EDUCAÇÃO EM EFICIÊNCIA ENERGÉTICA: CONSTRUINDO UM FUTURO SUSTENTÁVEL - Winik, Saul V.; Tonolo, Sandy; Franco, Guilherme F.; Bolacell, Julio C.; Sausen, Paulo S.; Campos, Mauricio d. (Salão do Conhecimento, 2013)
Resumo